Impacto da emissão dual-class na estrutura de capital - Lewandowski, Oscar (2013)
The thesis argues that companies with only voting shares use more debt than companies that issue both voting and non-voting shares. Taking into consideration the main theories of capital structure and the Brazilian reality, it was demonstrated the importance of relating debt to the fact of issuing shares without voting rights. Once the theoretical models, which manage to explain the firm‘s leverage level, still lack of explanatory power, the search for new determinants are present in the main capital structure literature. The occurrence of issuing shares in different classes (dual-class) as a factor that impacts on the debt-level was analyzed from three different points of view: market, industry and firms that pass through a unification process of its shares. The evidences found in the three investigations indicated that leverage is lower when preferred shares are issued, according to the trading environment and regulations in Brazil. The acceptance of the thesis has theoretical reflections in identifying a factor that could be taken into account in new models of capital structure, as well as, raises the importance of managers, investors and lenders to recognize the fact of being dual-class reflects not only in the firm‘s control structure, but also in its capital structure. Among the final considerations of the thesis was the recognition that companies listed on the Novo Mercado (Brazilian New Market Segment) in practice are, in the long run, changing the use of preferred shares for debt as a financing resource.